Modifikasi Rancangan Mesin Auto Button Insert Menggunakan Metode Quality Function Deployment - Dewin Purnama; Patricia Laetitia; Seto Tjahyono; Muslimin Muslimin (Jurnal Mekanik Terapan, 2023)
The development of industrial machinery is advancing with the progress of technology, especially in improving efficiency and product quality. PT. X is one of the electrical component production companies in Indonesia and is continuously striving for machine efficiency in its production. PT. X is developing one of its production machines, namely the auto button insert machine, as a pick and place machine in the assembly of temperature controllers. Modifying the design of the machine aims to reduce the cycle time for each product. Shortening the cycle time can result in one machine accommodating the needs of two new assembly lines that will be created. The previous machine's cycle time, which was 35 seconds per product, is shortened to 17 seconds using the Quality Function Deployment (QFD) method as the approach for designing the new machine. As a result, the cycle time reduction for this machine is 51%.